Regulating Financial Institutions: The Value of Opacity - Anand, Anita; Green, Andrew (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2012)
In this article, we explore a question of institutional design: What characteristics make a regulatory agency effective? We build on the growing body of administrative law literature that rigorously examines the impacts of transparency, insulation, and related administrative processes. We argue that there are certain benefits associated with an opaque and insulated structure, including the ability to regulate unfettered by partisan politics and majoritarian preferences. We examine Canada’s financial institution regulator, the Office of the Superintendent of Financial Institutions (OSFI), whose efficacy in part explains the resilience of Canada’s banking sector throughout the financial crisis of 2008. In particular, OSFI operates in a “black box”, keeping information about the formation of policy and its enforcement of this policy confidential. With its informational advantage, it is able to undermine the possibility that banks will collude or rent-seek. Our conclusions regarding the value of opacity cut against generally held views about the benefits of transparency in regulatory bodies.